The Effect of Acupressure on Clinical Stress Management in Nursing Students: A Randomised Controlled Study - Dilek Yildirim; Özlem Akman (Medical Association of Pharmacopuncture Institute, 2021)
Background : Nursing students experience clinical stress frequently and severely. The application of acupressure is reported to be effective in stress management.Objectives: This study was conducted to determine the effects of acupressure on reducing the stress of nursing students in clinical practice. Methods : This study was carried out using a single-blind randomized controlled experimental design. The experimental and control groups were randomly determined by using a previously prepared randomization checklist. A Participant Information Form, VAS, and the State Anxiety Inventory were applied to all students before practice. Acupressure was performed on the HT7 point and Yintang point (EX-HN3), respectively, every five minutes for a total of 30 minutes in the experimental group. Results : The level of stress experienced by the students in the experimental group before the intervention according to VAS was 6.95 ± 1.57, and it was determined as 2.82 ± 1.94 after the third application (p < 0.05). The mean clinical stress score before the application was 46.54 ± 3.81, and after the 3rd week of application, it was 25.15 ± 5.26 (p < 0.05). It was observed that the students' stress levels decreased in all measurements made after the acupressure intervention. Conclusion : This study determined that acupressure effectively reduces the stress levels of nursing students, and it may be applied in clinical stress management.